2008
DOI: 10.1158/0008-5472.can-08-1865
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylase Inhibition by α-Difluoromethylornithine Activates Opposing Signaling Pathways via Phosphorylation of Both Akt/Protein Kinase B and p27Kip1 in Neuroblastoma

Abstract: Ornithine decarboxylase (ODC) is a key enzyme in mammalian polyamine biosynthesis that is up-regulated in various types of cancer. We previously showed that treating human neuroblastoma (NB) cells with the ODC inhibitor A-difluoromethylornithine (DFMO) depleted polyamine pools and induced G 1 cell cycle arrest without causing apoptosis. However, the precise mechanism by which DFMO provokes these changes in NB cells remained unknown. Therefore, we further examined the effects of DFMO, alone and in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 38 publications
2
59
2
Order By: Relevance
“…AdoMetDC consumes SAM to produce aminopropyl groups for polyamine synthesis. It was thus possible that SAM depletion decreases polyamine pools and induces polyaminedepletion phenotypes, which are characterized by Akt activation, p27-dependent G1 arrest and p53-dependent apoptosis (Koomoa et al, 2009;Koomoa et al, 2008;Wallick et al, 2005). However, we did not detect any significant upregulation of p21, p27 or p53 levels during SAM checkpoint activation (supplementary material Fig.…”
Section: Q99lmentioning
confidence: 63%
See 1 more Smart Citation
“…AdoMetDC consumes SAM to produce aminopropyl groups for polyamine synthesis. It was thus possible that SAM depletion decreases polyamine pools and induces polyaminedepletion phenotypes, which are characterized by Akt activation, p27-dependent G1 arrest and p53-dependent apoptosis (Koomoa et al, 2009;Koomoa et al, 2008;Wallick et al, 2005). However, we did not detect any significant upregulation of p21, p27 or p53 levels during SAM checkpoint activation (supplementary material Fig.…”
Section: Q99lmentioning
confidence: 63%
“…In the case of methionine-free medium, RPMI 1640 medium was replaced with RPMI 1640 medium deficient in methionine, cysteine, and glutamine (R9016, US biological) and was supplemented with L-cysteine and L-glutamine at the same concentration as in standard RPMI 1640 medium. Medium supplemented with spermidine contained 1 mM aminoguanidine to inhibit serum polyamine oxidase (Koomoa et al, 2008). MK2 inhibitor MK2III was from Calbiochem (EMD Millipore, KGaA, Darmstadt, Germany).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…The efficacy of bortezomib is being assessed in individuals with (1) various hematological malignancies, who often receive bortezomib as part of multimodal chemo-or immunotherapeutic regimens (NCT02037256; NCT02112916; NCT02208037; NCT02312102); (2) neuroblastoma, who are treated with bortezomib plus difluoromethylornithine (a hitherto experimental inhibitor of polyamine biosynthesis), 148,149 (NCT02139397); and (3) various solid tumors, who receive bortezomib as standalone therapeutic agent or combined with standard chemotherapy (NCT02211755; NCT02220049) ( Table 2). …”
Section: Update On the Development Of Icd-inducing Chemotherapeuticsmentioning
confidence: 99%
“…In looking towards future clinical application, targeted therapies may be useful in combination with conventional chemotherapeutic agents in order to achieve synergistic effects, or alternatively, the combination of two targeted therapeutics may also prove efficacious. For example, recent studies have shown that DFMO acts synergistically with PI3 kinase inhibitors to increase apoptosis in neuroblastoma cells (Koomoa, Yco et al, 2008). Overall, despite the existing challenges in the discovery of new drugs, an increased understanding of cancer genetics is allowing the development of powerful drug or drug combinations that may increase the selectivity and safety of chemotherapy by selective killing of cancer cells and protecting normal cells.…”
Section: Future Perspectivesmentioning
confidence: 99%